Caracterización histopatológica de tumores mamarios en hembras caninas de la ciudad de Loja - Macas Palta, Jonathan Paul (2024)
Mammary tumors in female canines are the most common neoplasias and one of the main causes of mortality. Malignant neoplasias are diagnosed between nine to eleven years of age, while benign tumors are more frequent between seven and nine years. An adequate histopathological classification is essential, as it allows identifying the local extension of the neoplasia, its vascular invasion, the presence of necrosis, determining a prognosis and subsequent treatment. The purpose of this research was to perform the histopathological characterization of mammary tumors in female canines in the city of Loja, describing the histopathological characteristics and classifying them according to their origin and degree of malignancy. For this, 11 samples of neoplasias were collected at the “Cesar Augusto Guerrero” Veterinary Teaching Hospital of the National University of Loja, which were analyzed using conventional histological technique with hematoxylin and eosin staining. Through histopathological analysis, 6 types of neoplasias were identified, determining that 81.80% (9/11) are malignant tumors and 18.10% (2/11) are benign neoplasias. It was observed that mixed carcinoma was the most frequent, representing 45.45%, followed by carcinosarcoma (18.20%) and other types such as: lobular hyperplasia with fibrosis and secretory activity, fibroadenoma, anaplastic carcinoma, and chondrosarcoma, with 9.09% each. Additionally, the origin of the samples showed 72.73% mixed origin (mesenchymal and epithelial), 18.80% epithelial origin, and 9.09% mesenchymal origin. With a degree of malignancy of 81.81% (9/11), where 33.33% (3/9) corresponds to grade I, 66.67% (6/9) to grade II, without neoplasias in grade III. Of the analyzed samples, 6 neoplasias were identified, being mixed carcinoma (27.30%) and carcinosarcoma (18.20%) the most frequent, with a mixed origin of 72.73% (8/11) and grade II malignancy of 66.67%.